Application of the Lyapunov Exponent Based on Current Vibration Control Parameter ( CVC) in Control of an Industrial Robot - Szaniewski, Mateusz; Dąbrowski, Artur; Balcerzak, Marek; Zawiasa, Piotr (Wydawnictwo Politechniki Łódzkiej ; Katedra Dynamiki Maszyn - Wydział Mechaniczny Politechniki Łódzkiej, 2015)
Controlling dynamics of industrial robots is one of the most important and complicated tasks in robotics. In some works [3, 7], there are algorithms of the manipulators steering with flexible joints or arms. However, introducing them to calculation of trajectory results in complicated equations and a longer time of counting. On the other hand, works [4,5,6]show that improvement of the tool path is possible thanks to the previousidentification of the robot errors and their compensation. This text covers application of Largest Lyapunov Exponent (LLE) as a criterion for control performance assessment (CPA) in a real control system. The main task is to find a simple and effective method to search for the best configuration of a controller in a control system. In this context, CPA criterion based on calculation of LLE by means of a new method [9-11] is presented in the article.
Keywords: largest Lyapunov exponent; robot control; stability; nonlinear dynamics; największy wykładnik Lapunowa; sterowanie robotem; stabilność; dynamika nieliniowa